2019
DOI: 10.18016/ksutarimdoga.v22i45606.535882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals Pollution in Water and Sediments and Polychaetes in Sinop Shores of The Black Sea

Abstract: In this study four Polychaetes species namely Capitella capitata, Nereis zonata, Platynereis dumerilii and Perinereis cultrifera were selected to evaluate metal pollution in Karakum shores of Sinop Peninsula in the southern Black Sea. The Hg, Cd, Pb, Cu and Zn amounts in water, sediment as well as their existence in Polychaetes were studied to appraise the anthropogenic impact on their environment. Metals concentrations in water were found in the following order: Zn > Cu > Pb > Cd > Hg, whereas the order of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…These findings are probably related to environmental factors and the physiological activity of the animals. Furthermore, Bat et al (2019) showed a significant difference of metal accumulation between seasons in polychaetes on the shores of Sinop in the Black Sea.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are probably related to environmental factors and the physiological activity of the animals. Furthermore, Bat et al (2019) showed a significant difference of metal accumulation between seasons in polychaetes on the shores of Sinop in the Black Sea.…”
Section: Discussionmentioning
confidence: 92%
“…The sandworm ( Perinereis spp.) is the optimal macrofauna to be collected and used to detect Zn, Cu, Pb, and Cd in the sediment [ 45 , 46 ]. However, in the heavy metal concentration correlation analyses, only Mn was shown to be directly correlated between sediment and macrofauna ( r = 0.976; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%